2022
DOI: 10.1111/jfpp.16286
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted extraction of phenolic compounds from Capparis Ovata var canescens fruit using deep eutectic solvents

Abstract: The aim of this study is to develop a green procedure that provides high‐efficiency extraction of phenolic compounds from Capparis Ovata fruit with Deep Eutectic Solvent (DES) using ultrasound‐assisted extraction method. Ten DES combinations were prepared by mixing various proportions of choline chloride (ChCl), Na‐acetate and Na‐citrate with sugar alcohols, carboxylic acid. These DESs were tested as an effective solvent for recovering phenolic compounds. DES composed of lactic acid combining with ChCl showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…A significant change in extraction yield according to extraction time was observed, with no significant difference being found after 30 min. This result is in according with the result of previous studies [11,26,37,42]. Even though Wu et.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A significant change in extraction yield according to extraction time was observed, with no significant difference being found after 30 min. This result is in according with the result of previous studies [11,26,37,42]. Even though Wu et.…”
Section: Resultssupporting
confidence: 90%
“…It could be due to that adding water to DES could reduce viscosity, and lower viscosity led to higher mass transfer [19]. The same result was also found in previous studies [27,34,37,39]. Moreover, there wasn't any significant difference among DESs including various water content, with 70% DES + 30% water having the highest extraction yield than any combination of DES and water.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This behavior was opposite to that observed by Aksay et al [ 20 ], who found a lower content in brined and dry salted samples; however, the same authors affirmed that the polyphenol and flavonoid amounts decreased following the fermentation process. In fact, as reported in literature, their amount could be influenced by several factors such as the extraction and analysis methods, harvest regions, and processing since a portion of the polyphenols and flavonoids could be released into the brine or salt [ 14 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all the DES and conventional extracts Total Flavonoid Content (TFC) was evaluated according to the Aluminium Chloride method described by Ozbek & Ozmen (2022). Briefly, 0.5 mL of the extract, 2 mL of distilled water, and 150 μL NaNO 2 (5%, w/v ) were added to a volumetric flask.…”
Section: Methodsmentioning
confidence: 99%